Legal Power and Government Authority in the Implementation of Land Acquisition for Public Interest - Rezky Della Putri Waluyo; Amin Purnawan; Maryanto Maryanto (Sultan Agung Notary Law Review, 2021)
This study aims to analyze the legal strength and authority of local governments in the implementation of land acquisition for the public interest based on statutory regulations, to explain the constraints and solutions for implementing land acquisition for the public interest in Banyumas Regency. The approach method in this research is juridical empirical. The research specification used is descriptive analytical. Sources of data used in this study consist of primary data and secondary data which can be distinguished into primary legal materials, secondary legal materials, and tertiary legal materials. Collecting data in this study using literature study and interviews. The data analysis technique used is that the analyzed data will be presented in the form of qualitative data analysis. Based on this research, it can be concluded that the regulation of regional government authority in terms of land acquisition for the public interest is based on the provisions of Article 47 Paragraph (1) Presidential Regulation Number 148 of 2015 concerning Implementation of Land Acquisition for Development for Public Interest, the Governor with the authority he has can conduct land for public use. The governor in this case can carry out his own authority in the preparation of land acquisition or delegate it to the Regent and in the implementation of the authority of the regional government in land acquisition for public interest in Banyumas Regency, it is in accordance with Act No 2 of 2012 concerning Land Acquisition for Development for Public Interest, namely from the planning stage, the preparation stage, and implementation.